Fungicide timing for control of summer rots of apples - Everett, K.R.; Timudo-Torrevilla, O.E.; Taylor, J.T.; Yu, J. (New Zealand Plant Protection, 2007)
Control of preharvest summer rot in cv Royal Gala apple in the Waikato district during the 2006/2007 growing season was evaluated There were six treatments and an unsprayed control Three treatments investigated the effect of timing by applying tolyfluanid mancozeb captan and copper sequentially at 1014 day intervals in October and early November (spring) November and December (early summer) or January and February (late summer) The fourth treatment was two applications of carbendazim in early October (flowering) and there were two biological control treatments Bacillus subtilis QST713 and Serratia marcescens HR42 applied at 1014 day intervals from flowering (October) to harvest (February) Compared with the unsprayed treatment the most effective control was achieved by fungicide applications during either November/December or January/February Due to large variation in the data differences were not statistically significant but mean lesion diameter at final assessment for these treatments was 29 and 35 of controls respectively The other treatments did not control rots